A Bibliometric Analysis of Carbon Dots in Sensors Application - Putro, Permono Adi; Hardhienata, Hendradi; Isnaeni, Isnaeni; Ahmad, Faozan; Khaerudini, Deni Shidqi; Prasetyo, Andhika Prima; Maddu, Akhiruddin (Universitas Negeri Surabaya, 2022)
The exponential increase in carbonaceous-based research has prompted the scientific community to apply it to numerous value-added applications. This paper aimed to systematically analyze the comprehensive contributions clusters of publications per year, country, institution, authors, and keywords-wise by using a quantitative review technique called bibliometric analysis. The data was retrieved from the Scopus database to identify the overall scientific trend results with the keyword